2014
DOI: 10.1111/fare.12082
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Premarital Cycling on Early Marriage

Abstract: Using a sample of 564 newlywed couples and the enduring dynamics model of marriage, the study examined the impact of premarital cycling (breaking up and renewing) on the entrance into marriage and relationship dynamics over the first 5 years. Consistent with the enduring dynamics model, results demonstrated cyclical couples (compared to noncyclical couples) exhibited worse adjustment on a variety of relationship indicators at the entrance to marriage and were more likely to experience a trial separation over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 55 publications
2
33
0
Order By: Relevance
“…For example, cohabiting couples who experienced a breakup and renewal prior to cohabiting were more likely to currently report lower relationship satisfaction, greater uncertainty in the future of their relationship, and that child care was an important factor in their decision to cohabit than cohabiting partners who did not experience a breakup and renewal prior to cohabiting (Vennum et al, 2013). This pattern is mirrored at the transition to marriage, with newlyweds who ended and renewed their relationship prior to marriage being more likely to have considered calling off the engagement and reporting greater uncertainty in their decision to wed, less closeness, greater conflict, and less satisfaction than newlyweds with stable courtships (Vennum & Johnson, ).…”
Section: High‐ and Low‐risk Relationship Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, cohabiting couples who experienced a breakup and renewal prior to cohabiting were more likely to currently report lower relationship satisfaction, greater uncertainty in the future of their relationship, and that child care was an important factor in their decision to cohabit than cohabiting partners who did not experience a breakup and renewal prior to cohabiting (Vennum et al, 2013). This pattern is mirrored at the transition to marriage, with newlyweds who ended and renewed their relationship prior to marriage being more likely to have considered calling off the engagement and reporting greater uncertainty in their decision to wed, less closeness, greater conflict, and less satisfaction than newlyweds with stable courtships (Vennum & Johnson, ).…”
Section: High‐ and Low‐risk Relationship Developmentmentioning
confidence: 99%
“…About 30% to 50% of emerging adults (roughly ages 18–29; Arnett, ) have experienced at least one breakup and reconciliation with their current dating partner (a process termed relationship cycling , relationship churning , or on–off relationships ) and, compared to non‐cyclical partners, partners who have experienced a breakup and renewal report lower commitment and satisfaction, poorer communication, greater uncertainty, and higher levels of verbal abuse and physical violence (Dailey, Middleton, & Green, ; Dailey, Pfiester, Jin, Beck, & Clark, ; Dailey, Rosetto, Pfiester, & Surra, ; Halpern‐Meekin, Manning, Giordano, & Longmore, ). Unfortunately, the risks associated with relationship cycling during emerging adulthood appear to be enduring, affecting relationship stability and quality during later cohabitation and marriage (e.g., Vennum & Johnson, ). The lower dedication and greater uncertainty experienced by cyclical dating partners (e.g., Dailey, Pfiester, et al, ) may be due in part to less explicit decision making in their relationships.…”
mentioning
confidence: 99%
“…Research has found that young adults in churning relationships, compared with those in stably together or stably broken-up relationships, report more frequent conflict, lower levels of validation, lower levels of commitment, and higher levels of physical violence and verbal abuse (Halpern-Meekin et al 2013a, b). Other research has found that young adult churners report lower relationship satisfaction, feel less certain about the relationship’s future, and are less dedicated to their partners than their counterparts (Vennum and Johnson 2014; Vennum et al 2014, 2015). Qualitative research has also suggested that on/off relationships are frequently troubled, beset by issues such as conflict and infidelity (Cross-Barnett et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…More broadly, both level and rate of change in self‐esteem likely impact the long‐term health of intimate relations by determining the time at which partners are able to prioritize connection with a partner over the desire for self‐protection. Those motivated to connect early in a relationship (via high initial levels and/or rapid growth in self‐esteem) likely reap benefits years later, as dynamics at the outset of a relationship endure into the future (e.g., Caughlin & Huston, ; Vennum & Johnson, ).…”
Section: Introductionmentioning
confidence: 99%